Isothermal programming of triple shape memory. (18th August 2015) - Zhou, Jing; Li, Qiaoxi; Turner, Sara A.; Ashby, Valerie Sheares; Sheiko, Sergei S.
Abstract: Here we present a new strategy for enabling triple shape memory (TSM), in which different shapes may be programmed at one constant fixation temperature during isothermal crystallization of a poly(octylene adipate) elastomer. Unlike traditional TSM programming techniques that utilize separate thermal transitions to encode each distinct shape, here we report that multiple shapes may be encoded independently at different time stages of the same isothermal crystallization process, and then recovered sequentially at different temperatures upon heating. As such, the new method extends TSM capabilities to conventional semicrystalline elastomers that exhibit a single and narrow thermal transition. Unexpectedly, shape fixation does not depend on crystallinity acquired prior to sample deformation, which suggests that different shapes are secured by an individual crystalline scaffold with minor contribution of the pre-existing crystals. To that end, the isothermal protocol for TSM programming was utilized to demonstrate a "one-way reversible" shape memory transformation controlled by fixation time. Graphical abstract: Highlights: Programming multiple shapes isothermally at one constant temperature. Triple shape memory for polymers with narrow crystallization transitions. Individual shapes secured by distinct crystalline scaffolds. Demonstration of "one-way reversible shape memory". Maximization of reversible shape change with control of fixation time.